Experimental investigation on the effects of recycled aggregate on fracture behavior of polymer concrete - Reis,João Marciano Laredo dos (2011)
The sustainable management of solid wastes stimulates metallurgic and metal mechanics industries to look for safety applications for these wastes. The present paper examines the fracture behavior of polymer concrete (PC) manufactured with recycled foundry waste in substitution of fresh one. The recycled foundry sand is contaminated with polymer resin from the mold making process. Epoxy and unsaturated polyester resins were used as binder as cement substitute. The fracture results are analyzed by fracture energy; Gf, fracture toughness, K Ic, and the crack tip opening displacement, CTOD. It is found that the use of recycled foundry sand significantly influences the fracture properties. The use of recycled sand increase fracture toughness and similar fracture energy is observed. These results show that recycled sand is an excellent alternative as raw material.